Is virtual learning still virtually satisfactory in the post-COVID-19 era for pre-service teachers? - Sulaimon Adewale (Academy of Cognitive and Natural Sciences, 2024)
The planned global migration to the Fourth Industrial Revolution (4IR) and the unplanned incidence of the COVID-19 pandemic have necessitated the indispensability of virtual learning adoption in tertiary institutions. The success of virtual learning is premised on many factors, including the quality of virtual learning platforms (VLPs) and users' satisfaction. This study, therefore, examined the association between VLPs and pre-service teachers (PST) satisfaction in the post-COVID-19 era. The study adopted a quantitative design using multi-stage sampling to select 200 final-year students in education faculty. The analytical methods used were Pearson product-moment correlation and independent t-test using SPSS version 29 statistical software. The findings indicated a moderately positive link between the quality of virtual learning platforms and pre-service teachers' satisfaction. However, satisfaction levels differed based on the gender of the participants. This study recommends a regular collection of feedback from the students to identify where there are hitches; higher institutions should consider creating a quality assurance department for monitoring and evaluation of the institutions' virtual learning; and training and retraining of students and instructors are essential for the update of knowledge as the new technologies continue to emerge. The uniqueness of this study is in the appraisal of pre-service teachers' knowledge and satisfaction after the COVID-19 experience. There is no iota of doubt that pre-service teachers who are preparing to be engaged in different schools need to imbibe the culture of virtual learning. Therefore, further studies must be conducted on the best way to make virtual learning attractive.